Dual mobility total hip arthroplasty in the treatment of femoral neck fractures: a retrospective evaluation at mid-term follow-up - Canton, Gianluca; Moghnie, Alessandro; Cleva, Mirco; Kostoris, Francesco M; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Partial or total hip replacement is the method of choice for displaced femoral neck fractures (FNF) treatment. Dislocation is a major complication, accounting for about 3.8% of cases for hemiarthroplasty (HA) and 10% for total hip arthroplasty (THA). Dual-mobility (DM) socket in total hip arthroplasty showed a very low rate of dislocation in both primary and revision setting THA. Some literature reports show good results with low dislocation rates also in FNF treatment at short term follow-up. Aim of the study was to evaluate clinical and radiographic results of DM-THA in FNF treatment at mid-term follow up. Methods: Study population counted 31 implants in 30 patients treated with DM-THA for FNF between January 2010 and December 2012. Dislocation rate was identified, and HHS and OHS were completed. Twenty-four patients underwent also radiographic evaluation to assess cup integration and sings of loosening. Results: No episodes of hip dislocation nor intraprosthetic dislocation were found. Other postoperative complications were recorded in 9,67%. HHS and OHS showed a mean value of 81,22 and 37,37, respectively. There were no cases of clinical and radiographic signs of implant loosening. Conclusions: The present study confirms the good clinical results, low complications and very low dislocation rate with DM THA for FNF treatment.